Raising Students' Awareness of Cross-Cultural Contrastive Rhetoric Via an E-Learning Course - Jinghui Wang; Minjie Xing; Kenneth Spencer (Language Learning and Technology, 2008)
This study investigated the potential impact of e-learning on raising overseas students' cultural awareness and explored the possibility of creating an interactive learning environment for them to improve their English academic writing. The study was based on a comparison of Chinese and English rhetoric in academic writing, including a comparison of Chinese students' writings in Chinese with native English speakers' writings in English and Chinese students' writings in English with the help of an e-course and Chinese students' writings in English without the help of an e-course. Five features of contrastive rhetoric were used as criteria for the comparison. The experimental results show that the group using the e-course was successful in learning about defined aspects of English rhetoric in academic writing, reaching a level of performance that equalled that of native English speakers. Data analysis also revealed that e-learning resources helped students to compare rhetorical styles across cultures and that the interactive learning environment was effective in improving overseas students' English academic writing.